Implicit vs. explicit incentives : theory and a case study - Dominique M. Demougin; Oliver Fabel; Christian Thomann (Center for Economic Studies and ifo Institute (CESifo), 2009)
We derive the optimal contract between a principal and a liquidity-constrained agent in a stochastically repeated environment. The contract comprises a court-enforceable explicit bonus rule and an implicit fixed salary promise that must be self-enforcing. Since the agent's rent increases with bonus pay, the principal implements the maximum credible salary promise. Thus, the bonus increases while the salary promise and the agent's effort decrease with a higher probability of premature contract termination. We subject this mechanism to econometric testing using personnel data of an insurance company. The empirical results strongly support our theoretical predictions.
Keywords: J3; M5; 330; implicit contract; explicit bonus pay; premature contract termination; compensation and productivity estimates; Anreizvertrag; Implizite Kontrakte; Leistungsanreiz; Provision; Agency Theory; Theorie; Versicherungsvermittlung; Deutschland